HERITAGE OF THE PRAGUE SCHOOL TO CONTEMPORARY LANGUAGE TEACHING (WITH FOCUS ON ENGLISH LANGUAGE TEACHING) - Daniela Brevenikova (European Scientific Journal, ESJ, 2014)
The aim of the paper is to assess the heritage of the Prague School to contemporary linguistics and language teaching. In Chapter 1 the focus is on works and ideas two founding members of the Prague Linguistic Circle, Anglicists V. Mathesius and J. Vachek and their contribution to the development of Slovak and Czech linguistics as reflected in textbooks and course materials for undergraduates at Slovak and Czech universities. The continuation and extension of the Prague School functional and structural concept is documented with references to works of their followers up to the present days. Chapter 2 contains the analysis of selected parts of the PLC Theses (1929), namely sections related to application of PLC principles in secondary school language teaching. The ideas expressed in the late twenties and thirties of the 20th century are confronted with present-day practice of foreign-language learning and teaching.